Early electrodiagnosis in the management of neonatal brachial plexus palsy: A systematic review - Looven, Ruth; Le Roy, Laura; Tanghe, Emma; Broeck, Christine; Muynck, Martine; Vingerhoets, Guy; Pitt, Matthew; Vanderstraeten, Guy (Muscle & nerve, 2020)
Neonatal brachial plexus palsy (NBPP) is a prominent form of newborn morbidity with a potentially disabling persistence. Neurosurgical intervention is indicated in select NBPP patients. Early prognostic assessment would facilitate rational selection of those infants for surgery. We conducted a systematic literature review to determine the prognostic value of early electrodiagnosis (EDx) in NBPP. We included 16 observational studies with a total sample size of 747 children. Risk of bias and quality of evidence were rated. Wide variation was found in EDx techniques, outcome algorithms, and decisionmaking. Nevertheless, the most methodologically sound studies support the use of EDx, at standardized time‐frames, as a key prognostic modality for complementing clinical judgment and neuroimaging. An accurate knowledge of the underlying anatomy of the nerve injury helps to counsel families and to guide reconstructive strategy.